Aerobic test (7 x 200m) - Pyne, D.; Maw, G.; Goldsmith, W. (coachesinfo.com)
The aim of the test described here is to provide objective information on the aerobic or endurance fitness of the swimmer. The protocol involves a graded incremental test where cardiovascular (heart rate) and metabolic (blood lactate) responses to increasing speeds of swimming are measured. These data are processed using standard computer software for the generation of heart rate-velocity and lactate-velocity curves. The basic premise of this test is that heart rate and blood lactate responses to submaximal exercise are sensitive indicators of endurance fitness, and that blood lactate responses are related to training induced adaptations occurring within skeletal muscle (Weltman 1995). In practice, improvements in fitness are indicated by characteristic changes in the heart rate-velocity and lactate-velocity relationships.